Histological evaluation of testicles from prepubertal dogs submitted to vitrification with different cryoprotectant associations (Research, Society and Development, 2021)
The aim of this study was to histologically evaluate the testes of prepubertal dogs vitrified with different cryoprotectant associations. For this purpose, 10 testicles from prepubertal dogs were used, which were fragmented into samples of 1 to 2 mm3 and vitrified in different cryoprotectant associations: dimethylsulfoxide (DMSO)/ethylene glycol (EG), EG/glycerol(GLY) and DMSO/GLY. After a period of storage, the samples were warmed and subjected to classical histology and evaluated for cell separation of the basement membrane (SBM), basement membrane retraction (BMR), distinction between Sertoli cells and spermatogonia (DSS), nuclear visualization (NV) and nuclear condensation (NC). In all vitrified groups there was some degree of disorganization of the histological architecture compared to the control. The seminiferous tubules showed poorly developed germinal epithelium, rich in germ cells, good differentiation between spermatogonia and sertoli cells. The 3 vitrified groups had higher SBM compared to the control (P < 0.05) and did not differ from each other. All groups were similar to the control regarding BMR and NV. As for DSS, the DMSO/EG association did not differ from the control or from the EG/GLY association, however, this association and the DMSO/GLY association were significantly lower than the control, the latter being the worst result (P < 0.05). Regarding NC, EG/GLY did not differ from the control, nor from the DMSO/EG which, in turn, was inferior to the control (P < 0.05) and similar to the DMSO/GLY. It was concluded that the DMSO/EG and EG/GLY association were the ones that best preserved testicular integrity after the testicular vitrification process in prepubertal dogs.